Notes on Weibull Distribution - الوكيل علي عبد الحسين (Journal of Economics and Administrative Sciences, 2011)
Weibull Distribution is one of most important distribution and it is mainly used in reliability and in distribution of life time. The study handled two parameter and three-parameter Weibull Distribution in addition to five –parameter Bi-Weibull distribution. The latter being very new and was not mentioned before in many of the previous references. This distribution depends on both the two parameter and the three –parameter Weibull distributions by using the scale parameter (α) and the shape parameter (b) in the first and adding the location parameter (g)to the second and then joining them together to produce a distribution with five parameters. The paper also handled the relationship between Weibull Distribution and the other known distributions such as the exponential distribution, Chi distribution, Gamma distribution and Gumbel (extreme value) distribution. The paper considered a number of important notes including the importance and the application of Weibull distribution in the field of reliability. The study depended on the most recent research papers on this subject and until May 2004.